Survei vektor demam berdarah dengue di perumnas condong catur, kabupaten sleman, daerah istimewa yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
ABSTRAk Dengue is still an important problem in Indonesia and the case is reported every year from Perumnas Condong Catur. The absence of causative drugs and protective vaccines, therefore, indicates vector control measures as the only alternative for the disease abasement. Larva survey and placing ovitraps were done on August 1991 to determine the breeding habitats and the population densities of Aedes aegypti and Aedes albopictus in Perurnnas Condong Catur DIY. The results described that 20.77% of the containers were infested with Aedesaegypti larvae. The breeding sites induded water basins, earthen pitchers for keeping water, an old aquarium, a neglected flower vase and a flower pot made of an old can. The ovitrap index of Aedes aegypti in and outside the houses were 44.68% and 68.08% respectively. It was indicated too that only one ovitrap outside the house was infested with Aedes albopictus eggs.